Dissolution of calcium ion from teeth treated with different concentrations of siwak water extract in comparison with sodium fluoride - Nibal Mohammed Hoobi; Baydaa Hussein; Alhan Ahmed Qasim; Manhal Abdulrahman (College of Dentistry/ University of Baghdad, 2014)
Background: The miswak is a teeth cleaning twig made from a twig of the Salvadora persica tree (known as arak in Arabic).A traditional alternative to the modern toothbrush, it has a long, well-documented history and is reputed for its medicinal benefits. It also features prominently in Islamic hygienical jurisprudence. Materials and methods: Twenty maxillary first premolars were treated with the selected solutions which included siwak water extract (5%, 10%) and sodium fluoride 0.05% for 2minutes once daily for 20 days interval, deionized water was used as control negative. Then the concentration of the dissolved calcium ion in the etching solution of 2N HCL was measured. Results: The least amount of the dissolved calcium ion was registered for water siwak extract 10%, then sodium fluoride0.05%followed by water siwak extract5%. A significant difference was found between the two concentrations of siwak water extract, while no significant difference was recorded between the mentioned agents and sodium fluoride. There was highly significant difference between deionized water group and other groups except between water and siwak water extract5% the difference was significant. Conclusions: Siwak water extract is successful in improving tooth resistance against caries challenge as it mineralize and harden enamel surface.